Impact of Before and After Stock Split on Trading Volume Activity, Stock Returns, and Abnormal Returns : (Study on Companies Listed on the IDX in 2015-2019) - Akhmad Hendra Rahman; Bambang Widagdo; Titiek Ambarwati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
Capital market are venues where are channeled between the suppliers who have funds and those who are in need of capital. One of the corporate actions to influence the number of shares and share's value to attract the investor is stock split. To looking of the effect stock split of the company can be seen from trading volume activity, return, and abnormal return. In this research discusses the effect of the stock split events can affect trading volume activity, return of shares, and abnormal return by looking at the difference in trading volume activity, return of share, and abnormal return both before and after the stock split. Event window of this research which is 5 days before and 5 days after the stock split events. The data collected are historical data taken from various sources on the internet. The samples are based on purposive sampling, in this research using kolmogorov smirnov test for the normality data and using wilcoxon sign rank test to obtain the result. In this research declared that the stock split positively affects to trading volume activity. And the stock split will not affect both returns and abnormal returns.